Immuno-pathological Study of a Deprivation Effect on the Immune Response of Post-hatched Chicks - Alrawi , Saad Thabit Jassim; Jalob, Z. Kh. (International Journal of Poultry Science, 2018)
Objective: This study was conducted to investigate the effect of deprivation during the first few days of the post-hatch period on the immune response of chicks. Materials and Methods: One hundred and twenty one days old Ross 308 birds were used and they were divided into four groups, beginning with group 1 (G1): Direct feed supply, which was divided into 2 subgroups at 11 days of age with G1.a as a positive control and G1.b as a negative control. Groups 2, 3 and 4 experienced deprivation for 24, 48 and 72 h, respectively. Results: The results showed a significant (p<0.05) increase in antibody titre in G1 compared to that in G2 and G3 at 11 days of age, whereas at 21 days of age, G2 and G4 recorded a significant increase (p<0.05) in antibody titre compared to that in G1 and G3. The mortality rate significantly (p<0.05) increased in G1b compared to that in other groups. Histopathological study of the duodenum at 14 days of age showed that there were no developmental and functional differences between G1 and G2. In contrast, deprivation for 48 h (G3) showed a regenerative process, which was indicated by newly formed crypt cells in addition to the presence of congested mucosa. Deprivation for 72 h (G4) showed some compensatory growth in the form of hyperplasia of crypt cells and a congested muscular layer with inflammatory cells, but the cells did not attain their full size during G1 and G2. Conclusion: The study showed that an early feed supply had a direct effect on the immune status of the birds within 1-3 weeks. In addition, the study showed that an early supply creates a concrete communication with the digestive function of the gut but not at an older age.